Role of teacher learning agility: an empirical study for islamic educational success in Indonesia - Susanto, Susanto; Afif, Nur; Ritonga, Apri Wardana; Desrani, Ayu; Shunhaji, Akhmad; Ahmadi, Ahmadi (Intelektual Pustaka Media Utama, 2024)
This research aims to analyze the role of teacher learning agility in supporting the success of Islamic education in Indonesia. Researchers used a survey method distributed via a Google Form questionnaire. The population of this study were elementary, middle school, high school, bachelor’s and master’s level teachers, and a sample of 517 people was obtained, taken using random sampling techniques with the classification of 150 elementary school teachers, 135 middle school teachers, 148 high school teachers, 85 undergraduate lecturers, and 53 master level lecturers. The data were analyzed descriptively and measured using the analysis of variance (ANOVA) test assisted by the SPSS 22 program. The results of the research show that outstanding educators in Indonesia have high learning agility at work. More than 50% of respondents respond to current developments and apply learning agility in the workplace. Based on job classification, lecturers have higher learning agility with an overall average of above 4.20. Meanwhile, based on gender, women are superior to men in its application. Educators with learning agility display maximum work performance, are able to draw lessons from work experience, adapt to change with full awareness and enthusiasm for learning to improve their skills, knowledge and competence.